The Usage of Taboo in Sukabumi Society - Lusi Susilawati1, Lusi Susilawati1; Gugun, Gunardi; Elvi, Citraresmana; Dian, Indira (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Taboo is a social prohibition; it does not only relate to forbidden acts but also words (Fromkin, Rodman, & Hyams, 2003). It means that when an act is considered to be taboo, then all related acts are also taboo including when they are talking about it. Currently, technology is developing rapidly, and the development of technology results in the development of language, such as the emergence of some new words. Stockwell & Mintoka (2001) revealed that the sources of new words are from borrowing and word creation. Therefore, some people are more acquainted with new words than local ones. Such a condition could easily shift the local language. It is concluded that the development of technology is one of the causes of regional language shift. Moreover, the development of language could also transform the knowledge and belief system of a society. Qismullah & Yusuf (2014) in their research found that Acehnesse people have a change in habits, ideas, values, and behaviour caused by the development of education and communication technologies.